Bilateral substrate effect on the thermal conductivity of two-dimensional silicon. Issue 14 (12th March 2015) - Zhang, Xiaoliang; Bao, Hua; Hu, Ming
Abstract : Thermal conductivity of silicene can be either enhanced or suppressed by changing the surface crystal plane of the substrate, which is fundamentally different from the general understanding of supported graphene. Abstract : Silicene, the silicon-based counterpart of graphene, has received exceptional attention from a wide community of scientists and engineers in addition to graphene, due to its unique and fascinating physical and chemical properties. Recently, the thermal transport of the atomic thin Si layer, critical to various applications in nanoelectronics, has been studied; however, to date, the substrate effect has not been investigated. In this paper, we present our nonequilibrium molecular dynamics studies on the phonon transport of silicene supported on different substrates. A counter-intuitive phenomenon, in which the thermal conductivity of silicene can be either enhanced or suppressed by changing the surface crystal plane of the substrate, has been observed. This phenomenon is fundamentally different from the general understanding of supported graphene, a representative two-dimensional material, in which the substrate always has a negative effect on the phonon transport of graphene. By performing phonon polarization and spectral energy density analysis, we explain the underlying physics of the new phenomenon in terms of the different impacts on the dominant phonons in the thermal transport of silicene induced by the substrate: the dramatic increase in the thermal conductivity of silicene supported on the 6H-SiC substrate is due to the augmented lifetime of the majority of the acoustic phonons, while the significant decrease in the thermal conductivity of silicene supported on the 3C-SiC substrate results from the reduction in the lifetime of almost the entire phonon spectrum. Our results suggest that, by choosing different substrates, the thermal conductivity of silicene can be largely tuned, which paves the way for manipulating the thermal transport properties of silicene for future emerging applications.